Abbazie e paesaggi medievali in Toscana - Corsani, Gabriele; Rombai, Leonardo; ZOPPI, Maria Concetta (Territori, 2014)
The volume collects the contributions of the 'study day' held on June 16, 2010 at the University of Florence on Abbeys and medieval landscapes in Tuscany, that is, on the forms of the territory that have structured the ways of life in the countryside of our region for centuries. Today an infatuation is observed for that kind of landscape, which is confirmed by a lack of interest for its conservation or for transformations respectful of the rules that produced it. It is therefore appropriate to submit to the historic method a synthetic view of the medieval landscape, from the ancient premises to the economic reasons that led to the monastic and feudal forms, up to the appearance of a new structure appreciated for its useful beauty, in a persistent substratum of mysterious storytelling. Tuscany allows multiple evidence of what actually survives of the pervasive order established in the Middle Ages also for its exemplary literary and iconographic representations, both contemporary and of the medieval times.